2023
DOI: 10.31219/osf.io/qtez8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in the heartbeat-evoked potential under ventricular fibrillation: a near-death case report

Abstract: Background & Purpose: Whether brain-heart communication continues under ventricular fibrillation (VF) remains to be acknowledged. There is limited evidence of the physiological changes in cortical activity under VF. Moreover, brain-heart communication has not been studied before in this condition. We aim to illustrate parallel changes in heart-rate variability, cortical activity, and brain-heart interactions in a case report undergoing VF. Methods: The case report's EEG and EKG was acquired for approxi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Different animal models have shown that towards the near-death, baseline (intracranial) EEG and heart rate are reduced in parallel 65,66 . These effects are reported in human near-death case reports, where the brain’s cessation of activity occurs in parallel or after the autonomic cessation 39,45 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Different animal models have shown that towards the near-death, baseline (intracranial) EEG and heart rate are reduced in parallel 65,66 . These effects are reported in human near-death case reports, where the brain’s cessation of activity occurs in parallel or after the autonomic cessation 39,45 .…”
Section: Discussionmentioning
confidence: 86%
“…So far, the assessment of ANS dysfunction mostly relied on various HRV metrics notably in the frequency domain with two main frequency bands of interest in short recordings: HF band (i.e., 0.15 to 0.4 Hz) predominantly reflecting the parasympathetic tone, and LF (i.e., 0.04 to 0.15 Hz) primarily mediated by sympathetic activity, although both metrics are susceptible to changes in parasympathetic and sympathetic activity 37 . However, so far, studies have either focused on HRV metrics alone 24 or the cortical integration of heart signals using HEPs 38,39 . We here show that the study of bilateral brain-heart interactions is more comprehensive in evaluating ANS function after CA by providing mechanistic insights into the pathophysiology of HIBI.…”
Section: Discussionmentioning
confidence: 99%